Wild strawberries : a novel - Thirkell, Angela, 1890-1961 (Moyer Bell, 2005)
Witty romp through English Country-house life at its most delightfully absurd. At Rushwater House in West Barsetshire, Lady Emily Leslie and her family are entertaining an assortment of house guests, hangers-on, and French monarchists. Amid a perfect welter of rapturous embraces and moonlight madness, a marriage is finally arranged. A glittering summer party provides an hilarious climax to the various intrigues.